2017
DOI: 10.1186/s40352-017-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Contributors to nonsuicidal self-injury in incarcerated youth

Abstract: BackgroundDespite elevations in risks associated with self-injurious behavior among community adolescents, the degree to which these features are associated with self-injury among incarcerated youth has rarely been examined. Although the DSM-5 recently proposed a distinct category of nonsuicidal self-injury (NSSI), most studies of youths in forensic settings have not distinguished between subtypes of self-harming individuals.MethodsDemographic, offense, and disorder contributors to NSSI in incarcerated youths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Somewhat similar risk factors for NSSI have been observed for justice-involved youth. The dominant risk factors are abusive past life experiences and current adverse life events, younger age, substance use, dissociation, and previous self-harm and suicide attempts (Kenny et al, 2008; Matsumoto et al, 2005; McReynolds et al, 2017).…”
mentioning
confidence: 99%
“…Somewhat similar risk factors for NSSI have been observed for justice-involved youth. The dominant risk factors are abusive past life experiences and current adverse life events, younger age, substance use, dissociation, and previous self-harm and suicide attempts (Kenny et al, 2008; Matsumoto et al, 2005; McReynolds et al, 2017).…”
mentioning
confidence: 99%
“…This finding is underpinned by earlier studies where depressive symptoms were highly comorbid with NSSI ( 13 , 83 ). In incarcerated adolescents, MDD symptoms were found among those who reported NSSI twice as often compared to those without a history of self-injury ( 84 ). It is not clear why we obtained different results (significant and non-significant) when we assessed the association between NSSI and depression using different measures.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐harm is defined as the deliberate destruction or alteration of body tissue without conscious suicidal intent (Favazza, 1989; Nock & Favazza, 2009). Prevalence estimates for self‐harm in adolescence range from 13.9% to 21.4%, with higher estimates found in adolescents who have experienced trauma from abuse, incarceration, or human trafficking (Kiss et al, 2015; McReynolds et al, 2017; Moreno et al, 2016; Nock & Favazza, 2009; Patchin & Hinduja, 2017; Wang et al, 2017). A meta‐analysis of studies published between 1990 and 2015 on adolescent self‐harm found that the mean age of starting self‐harm was 13 years, with 47% reporting only one or two episodes, and cutting being the most common type (45%) (Gillies et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐harm during adolescence carries risk of depression/anxiety, delinquency/aggressive behavior, suicide, alcohol/drug use, poor school performance, dysfunctional interpersonal relationships, and physical scarring (Kiss et al, 2015; McReynolds et al, 2017; Nock & Favazza, 2009). Suicide shares many of the same risk factors as self‐harm, with elevated risk of both behaviors occurring in 15‐ to 19‐year‐old youth (Hawton et al, 2012; Hilton, 2017).…”
Section: Introductionmentioning
confidence: 99%